Langkah-Langkah Pelaksanaan Guru PAI dalam Peningkatan Efektifitas Pembelajaran Baca Tulis Al-Quran - Okta Khusna Aisi (LP2M Sekolah Tinggi Agama Islam Nahdlatul Ulama Pacitan, 2020)
Given the importance of the ability to read the Qur’an to students , so here the teacher must continue to try to motivate students to be enthusiastic in learning to read and write the Qur’an. Planting, training, and fostering islamic education in this case education or reading and writing lessons of the Qur’an is not only the responsibility of a teacher of the koran or religious teacher at school, more than that all parties are obliged to realize and advance a society that is able to read and writing the Qur’an. The role of a teacher in delivering lessons to improve the ability to read and write the Qur’an also needs a teacher to choose the right method in teaching and learning strategies. Along with the progress of the present age, teaching methods are developing rapidly from the simple to the more practical, from the complicated to the easy using a relatively short time. Among the methods that have been used, among others, iqra method, and so forth.